Penerapan metode Travelling Salesman Problem (TSP) dengan algoritma branch and bound pada optimasi rute terpendek distribusi surat di Dinas Pendidikan dan Kebudayaan Kota Malang - Sulastri, Sulastri (Maliki Interdisciplinary Journal, 2024)
In the modern world, time efficiency in organizations, including government institutions, is crucial. The Department of Education and Culture of Malang City faces challenges in distributing letters between work units quickly to ensure smooth administration. Therefore, finding an optimal route for letter distribution is essential. The Travelling Salesman Problem (TSP) is relevant to this issue, with the Branch and Bound Algorithm used to find the shortest route. This algorithm systematically explores all routes and eliminates unnecessary options, allowing the optimal solution to be reached more quickly. This research employs a quantitative approach and field study at the Department of Education and Culture of Malang City, resulting in the shortest route: Surat Menyurat → Umum → Ketenagaan → Keuangan → PAUD → Pendas → Perencanaan → Kebudayaan → Surat Menyurat, with a travel time of 12.5 minutes. The Branch and Bound Algorithm has proven effective in optimizing the letter distribution route. Future research is suggested to expand the study object to compare the accuracy of this algorithm in finding the shortest route.